HUBUNGAN ANTARA PERHATIAN ORANG TUA DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS IX SMP NEGERI 20 PALU - Hasnita I Labangsa; Ibnu Hadjar (Jurnal Elektronik Pendidikan Matematika Tadulako, 2021)
This study aims to determine how much parental attention is paid to class IX students at SMP Negeri 20 Palu and to determine a significant relationship between parental attention and mathematics learning achievement of class IX students at SMP Negeri 20 Palu. This research is a quantitative approach using a correlational design. The population of this study were all grade IX students of SMP Negeri 20 Palu, totaling 154 students. The research sample was obtained using the purposive sampling technique, the number of students who became the sample was 60 students. The data collection technique used parental attention questionnaires and documentation of mathematics learning achievement from student report cards. Based on the results of data analysis, it was obtained that the average parental attention variable was 69.73 (scale 25 - 100) included in the criteria for sufficient attention. The average variable of student learning achievement in mathematics is 81.77 (scale 0 – 100) in the high criteria. Furthermore, the results of data analysis using the product moment correlation test obtained a correlation value of r = 0.402 and a significance value (sig(2-tailed)) of 0.001. This means that there is a significant relationship between parental attention and mathematics learning achievement of class IX students of SMP Negeri 20 Palu.